Does socioeconomic inequality occur in the multimorbidity among Brazilian adults? - Ândria Krolow Costa; Andréa Dâmaso Bertoldi; Andréia Turmina Fontanella; Luiz Roberto Ramos; Paulo Sergio Dourado Arrais; Vera Lucia Luiza; Sotero Serrate Mengue; Bruno Pereira Nunes (Revista de Saúde Pública, 2020)
ABSTRACT OBJECTIVE: To assess the prevalence of multimorbidity among Brazilian adults and its association with socioeconomic indicators. METHODS: Cross-sectional study that used data from the Pesquisa Nacional Sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos no Brasil (PNAUM – Brazilian National Survey on Access, Use and Promotion of Rational Use of Medicines), carried out between 2013 and 2014. The definition of multimorbidity was the coexistence, in a single individual, of two or more chronic diseases, measured through a list of 14 morbidities (self-reported medical diagnosis throughout life). Economic status and educational level were the socioeconomic indicators used, being the inequalities assessed through the Slope Index of Inequality (SII) and the Concentration Index, stratified by gender. RESULTS: The study comprehended 23,329 adults (52.8% of which were women), with an average age of 37.9 years. Hypertension and high cholesterol levels were the most prevalent conditions. The prevalence of multimorbidity was of 10.9% (95%CI 10.1–11.7) representing nearly 11 million individuals in Brazil, of which 14.5% (95%CI 13.5–15.4) were women and 6.8% (95%CI 5.9–7.8) were men. The occurrence of multimorbidity was similar according to the socioeconomic indicators. In the inequality analysis, we observed absolute and relative differences in men with a higher purchasing power (SII = 3.7; 95%CI 0.3–7.0) and higher educational level (CIX = 7.1; 95%CI 0.9–14.7), respectively. CONCLUSIONS: The frequency of comorbidities in Brazilian adults is high, especially in absolute terms. We only observed socioeconomic inequalities in multimorbidities among men.